Guiding organs-on-chips towards applications: a balancing act between integration of advanced technologies and standardization - Meneses, J.; Conceição, F.; van der Meer, A. D.; de Wit, S.; Moreira Teixeira, L. (Frontiers in Lab on a Chip Technologies, 2024)
Organs-on-chips (OoC) are in vitro models that emulate key func4onali4es of 4ssues or organs in a miniaturized and highly controlled manner. Due to their high versa4lity, OoC have evolved as promising alterna4ves to animal tes4ng, toward a more effec4ve drug development pipeline. Addi4onally, OoC are revealing increased predic4ve power for toxicity screening applica4ons, as well as (patho-)physiology research models. It is an4cipated that enabling technologies such as biofabrica4on, mul4modality imaging, and ar4ficial intelligence, will play a cri4cal role in the development of the next genera4on of OoC. These domains are expected to increase mimicry of human micro-physiology and func4onality, enhance screening of cellular events, and generate high-content data for improved predic4on. Although in exponen4al growth, the OoC field will strongly benefit from the implementa4on of standardiza4on tools to upgrade its implementa4onal power. The complexity derived from the integra4on of mul4ple technologies and the current absence of concrete guidelines to establish standards, may be the reason for slower adop4on of OoC in industrial se]ngs, despite the fast progress of the field. In this perspec4ve, we argue that it is essen4al to consider standardiza4on early on when using new enabling technologies, and we provide examples to illustrate how to maintain a focus on technology standards as these new technologies are used to build innova4ve OoC applica4ons. Moreover, we stress the importance of informed design, use and analysis decisions. Finally, we argue that this early focus on standards in innova4on for OoC will facilitate their implementa4on.